User modeling for people with special needs. Issue 3 (26th August 2014) - Kurschl, Werner; Augstein, Mirjam; Burger, Thomas; Pointner, Claudia
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to present an approach where a novel user modeling wizard for people with motor impairments is used to gain a deeper understanding of very specific (touch-based and touchless) interaction patterns. The findings are used to set up and fill a user model which allows to automatically derive an application- and user-specific configuration for natural user interfaces. Design/methodology/approach – Based on expert knowledge in the domain of software/user interfaces for people with special needs, a test-case –based user modeling tool was developed. Task-based user tests were conducted with seven users for the touch-based interaction scenario and with five users for the touchless interaction scenario. The participants are all people with different motor and/or cognitive impairments. Findings – The paper describes the results of different test cases that were designed to model users' touch-based and touchless interaction capabilities. To evaluate the tool's findings, experts additionally judged the participants' performance (their opinions were compared to the tool's findings). The results suggest that the user modeling tool could quite well capture users' capabilities. Social implications – The paper presents a tool that can be used to model users' interaction capabilities. The approach aims at taking over some of the (very time-consuming) configuration tasks consultants have to do to configure software according to the needs of people with disabilities. This can lead to a wider accessibility of software, especially in the area of gesture-based user interaction. Originality/value – Part of the approach has been published in the proceedings of the Interactional Conference on Advances in Mobile Computing and Multimedia 2014. Significant additions have been made since (e.g. all of the touchless interaction part of the approach and the related user study).